Aromatic Oligoamides with a Rare ortho‐Connectivity: Synthesis and Study of ortho‐Arylopeptoids. Issue 17 (7th May 2013) - Hjelmgaard, Thomas; Nielsen, John
Abstract: Even though aromatic oligoamides composed of aromatic amino acids in a "one‐way sequence" attract ever increasing research interest, backbones connected through ortho ‐linked aromatics remain rare. Herein, we present the first synthesis and study of N ‐alkylated ortho ‐aminomethyl‐benzamides termed " ortho ‐arylopeptoids". The ortho ‐arylopeptoids may, with a few exceptions, be synthesized either in solution or on solid‐phase using unique and highly efficient submonomer methods with similar levels of high generality and efficiency to those previously demonstrated for meta ‐ and para ‐arylopeptoids. NMR studies indicated a more restricted rotation about the amide bonds in ortho ‐arylopeptoids, presumably due to a more congested backbone structure resulting from the ortho ‐connectivity pattern. Intriguingly, tert ‐butyl and phenyl side chains offer complete control over the amide conformations; whereas arylopeptoid residues with tert ‐butyl side chains adopt a 100 % cis amide conformation, the opposite 100 % trans amide conformation was observed in arylopeptoids with phenyl side chains. The tert ‐butyl moiety can furthermore serve as a protecting group during synthesis, which can later be removed to allow the amide to adopt a 100 % trans conformation instead. Abstract : We present the first synthesis and study of N ‐alkylated ortho ‐aminomethyl‐benzamides termed " ortho ‐arylopeptoids". These compounds can be synthesized both on solid‐phase and in solution using a unique submonomer method and constitute a rare example of aromatic oligoamides with ortho ‐connectivity. The tert ‐butyl and phenyl side chains offer complete control over the amide conformations.